2004
DOI: 10.1080/08039480310000752
|View full text |Cite
|
Sign up to set email alerts
|

Childhood sexual abuse. Women's health when starting in group therapy

Abstract: Childhood sexual abuse has been shown to be common among adult women, 15-30% in prevalence studies, and among mentally ill women, 25-77%. These women often suffer from depression, anxiety, sexual and relationship problems. Suicide attempts and self-destructive behaviour are common. Within the Department of Psychiatry at Lund University Hospital, 45 women with experiences of childhood sexual abuse were offered a 2-year-long trauma-focused group therapy. They were well educated but 27% were unemployed. Nearly ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…It is of interest to further investigate how the development of sense of coherence may be affected by SA and how psychological treatment of children and adolescents exposed to SA may change their sense of coherence. Lundqvist (34) showed that SOC had increased after treatment in a clinical sample with women exposed to SA, even if the scores at a group level still were lower than the scores of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest to further investigate how the development of sense of coherence may be affected by SA and how psychological treatment of children and adolescents exposed to SA may change their sense of coherence. Lundqvist (34) showed that SOC had increased after treatment in a clinical sample with women exposed to SA, even if the scores at a group level still were lower than the scores of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, in a study of 2,300 18‐year‐old females in Sweden, Svedin and Priebe () reported a prevalence of CSA (including penetration) at 13.5 per cent. The number of unrecorded cases is most likely quite high because many victims do not disclose the abuse, neither as children nor as adults (Lundqvist et al., ). Regarding disclosure patterns, Hébert et al.…”
Section: Introductionmentioning
confidence: 99%
“…Group therapy affords members the opportunity to share their victimisation experiences with other survivors in a secure setting, reducing isolation and stigmatisation, and creating a supportive network. This directly counteracts the lonely experience of CSA and contributes to a reframing of personal identity from lone victim-child to collective powerful survivor-adult Lundqvist et al, 2004). Meekums (2000:71) refers to this element of group therapy as "witnessing", a sense of being benevolently seen, heard and understood in the presence of others.…”
Section: Group Treatmentmentioning
confidence: 99%
“…Although some researchers found little evidence regarding the effectiveness of individual versus group therapy (Martsolf & Draucker, 2005), there is a strong body of research supporting group therapy in the treatment paradigm of adult survivors of CSA, specifically given its potential to reduce stigma and its cost-effectiveness (Brown, Reyes, Brown & Gonzenbach, 2013Lundqvist, Svedin & Hansson, 2004).…”
Section: Group Treatmentmentioning
confidence: 99%
See 1 more Smart Citation